(untitled) (Research, Society and Development, 2021)
The economic viability analysis is essential due to its use as a parameter for the correct decision making. The objective of this study was to analyze the economic viability of japanese pumpkin production in the region of Iporá, Goiás, due to its socioeconomic relevance, based on local family farming. In this way, the cost of production and crop income during a cycle for the cultivars ’Japonesa F1’, ’Kyoto’, ’HC 01’ and ’HC 02’ were elaborated. Afterwards, the Net Present Value (NPV), the Internal Rate of Return (IRR) and the Payback were determined according to the tools of economic feasibility analysis. The results of the economic viability were determined from the agronomic performance of the cultivars. The NPV, IRR and Payback tools were positive, verifying the feasibility of the investment in both cultivars. However, the results show that among the analyzed cultivars, the most outstanding was ’HC 01’ in terms of productivity, cost of production 0.56 R/kg, NPV was positive of R 2,457.75, the IRR was 18,67% per month and Payback for 3 months.